Political psychology and polarisation: A conceptual approach - GEÇER, EKMEL (My University, 2023)
This study, mostly in a theoretical way and through a descriptive textual analysis, aims to give insights into the digital divide within the context of political and media psychology. The article creates new concepts and theories, and relates them to the conflicts on online platforms and tries to present the socio-cultural background that reinforces online polarisation based on new media and communication theories. The article discusses cultural psychology as the main motive for digital polarisation and touches upon online behaviour patterns that are considered as the driving force of rigid politicisation. Starting from this point of view, this conceptual study attempts to answer how the digital divide plays a role as a root cause or intervening factor in conflict and resolution issues and state-society relations. This work then aims to shed valuable light on the dynamics of peace and political psychology in reducing digital polarization and how terms related to socio-cultural psychology like contact theory may increase intimacy and reduce prejudices towards the other which are most likely caused by the echo chambers created on the online platforms. Therefore, this theoretical research, uncovering the potential of peace psychology and drawing upon the relevant existing literature, has important implications for reducing political polarization, the digital divide in other words, on online media platforms which will also help overcome conflicts and discriminations in daily political lives.
Keywords: Sosyal ve Beşeri Bilimler; Social Sciences and Humanities; Sosyal Bilimler (SOC); Social Sciences (SOC); Digital Divide; Polarisation; Political and Peace Psychology